2016
DOI: 10.1037/xlm0000277
|View full text |Cite
|
Sign up to set email alerts
|

The role of feedback contingency in perceptual category learning.

Abstract: Feedback is highly contingent on behavior if it eventually becomes easy to predict, and weakly contingent on behavior if it remains difficult or impossible to predict even after learning is complete. Many studies have demonstrated that humans and nonhuman animals are highly sensitive to feedback contingency, but no known studies have examined how feedback contingency affects category learning, and current theories assign little or no importance to this variable. Two experiments examined the effects of continge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 68 publications
3
18
0
Order By: Relevance
“…In the context of our suggestion to use maximum likelihood, there is a certain irony in that fact that the most recent COVIS papers tend to use the Bayesian Information Criterion (e.g., Ashby & Vucovich, ; Spiering & Ashby, ), while earlier papers tended to use the Akaike Information Criterion (Ashby et al., ; Ell et al., ; Maddox, Bohil, & Ing, ; Maddox & Ing, ). This is because both information criteria attempt to correct for model complexity using the number of parameters and the BIC penalizes high‐parameter models more heavily than the AIC (Myung & Pitt, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the context of our suggestion to use maximum likelihood, there is a certain irony in that fact that the most recent COVIS papers tend to use the Bayesian Information Criterion (e.g., Ashby & Vucovich, ; Spiering & Ashby, ), while earlier papers tended to use the Akaike Information Criterion (Ashby et al., ; Ell et al., ; Maddox, Bohil, & Ing, ; Maddox & Ing, ). This is because both information criteria attempt to correct for model complexity using the number of parameters and the BIC penalizes high‐parameter models more heavily than the AIC (Myung & Pitt, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, despite all these critiques, proponents of COVIS still publish studies looking to find a dissociation between learning of rule‐based and information‐integration category structures (e.g., Ashby & Vucovich, ; Smith et al., , ) and strongly recommend these category structures as appropriate for studying category learning (Ashby & Valentin, in press). It is these most recent (and future) studies that the work presented here most targets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within my field, the psychology of concepts, this became apparent in the many studies of the classic debate between prototype and exemplar models, when it was eventually realized that group results did not necessarily represent the individuals making up the group. When models were fit to individual subjects, it was often found that some people were fit by prototype models, some by exemplar models, and some by no model (e.g., Malt, ; Smith, Murray, & Minda, ; see also a different comparison by Ashby & Vucovich, ). Variation is found in other conceptual behaviors.…”
Section: The Way In Which Fodor Was Rightmentioning
confidence: 99%
“…Contrast this with veridical feedback, in which negative feedback is typically accompanied by low response confidence. We recently showed that category learning is exquisitely sensitive to this feedback contingency (Ashby & Vucovich, in press). (2) The TANs must close the gate when RF is detected.…”
Section: Introductionmentioning
confidence: 99%